Solution Focused Approach and Usage of Nursing - Nurcan AKGUL GUNDOGDU; Handan ZINCIR; Nuran GULER (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
"Problem talk creates problems; solution talk creates solutions " Steve de Shazer